Changes of Number and Function of Late Endothelial Progenitor Cells in Peripheral Blood of COPD Patients Combined with Pulmonary Hypertension - Liu, Pei; Zhang, Hongmei; Liu, Jianxin; Sheng, Chunfeng; Zhang, Linlin; Zeng, Yanjun (The Thoracic and Cardiovascular Surgeon, 2016)
Objective The objective of this study was to investigate the changes of number and function of late endothelial progenitor cells (EPCs) in peripheral blood of chronic obstructive pulmonary disease (COPD) patients combined with pulmonary hypertension.Subjects and Methods The study enrolled 120 cases including 40 non-COPD and pulmonary arterial hypertension (PAH) patients (non-COPD group), 40 COPD non-PAH patients (COPD group), and 40 COPD patients combined with PAH (COPD + PAH group). Peripheral blood mononuclear cells were separated by density gradient centrifugation, cultured for 21 days, and then identified as late endothelial progenitor cells. The cell colonies were counted. MTT assay, modified Boyden chamber assay, and human fibronectin plates were used to measure the proliferation, migration, and adhesion functions of the late endothelial progenitor cells, respectively.Results Compared with non-COPD and COPD groups, the number of peripheral blood late EPCs in COPD + PAH group was significantly reduced, and the proliferation, adhesion, and migration capacities were significantly lowered; the differences were statistically significant (p < 0.05). The number and function of late EPCs decreased with the increase of pulmonary artery pressure (p < 0.05).Conclusion The number of late EPCs in COPD patients combined with pulmonary hypertension was reduced, which implies the impaired cell functions. The changes of number and function were negatively correlated with the severity of pulmonary hypertension.
Keywords: chronic obstructive pulmonary disease; pulmonary hypertension; late EPCs